2018
DOI: 10.1080/14616696.2018.1442929
|View full text |Cite
|
Sign up to set email alerts
|

Nudging gender desegregation: a field experiment on the causal effect of information barriers on gender inequalities in higher education

Abstract: In this article, we propose and test a novel explanation for gender segregation in Higher Education that focuses on the misperceptions of economic returns to fields of study. We frame this explanation within the literature emphasizing the role of gender-stereotypical preferences and occupational plans, and we argue that counselling activities in school can play a crucial role in either reinforcing or countering the weight of these expressive mechanisms relative to more instrumental considerations involving occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
(29 reference statements)
4
25
0
Order By: Relevance
“…Yet we have to keep in mind that our intervention took place late in the school career and was of short duration. Thus, earlier and more intensive interventions might be more successful in this respect (e.g., Barone et al, 2019). Moreover, another result from our study is also more promising: As reported above (Section 4.3), overall our information intervention increased the college application rates of those who intended to apply to college at the end of the penultimate school year but not of those who intended to start an apprenticeship.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Yet we have to keep in mind that our intervention took place late in the school career and was of short duration. Thus, earlier and more intensive interventions might be more successful in this respect (e.g., Barone et al, 2019). Moreover, another result from our study is also more promising: As reported above (Section 4.3), overall our information intervention increased the college application rates of those who intended to apply to college at the end of the penultimate school year but not of those who intended to start an apprenticeship.…”
Section: Discussionsupporting
confidence: 63%
“…They mostly provide information on the costs of, and returns to, different kinds of education and test its effect on HE intentions and decisions (e.g., Barone, Schizzerotto, Abbiati, & Argentin, 2017;McGuigan et al, 2016;Oreopoulos & Dunn, 2013). Although some studies also look at the impact of information on major choices (Barone et al, 2019;Hastings et al, 2015;Kerr et al, 2015;Wiswall & Zafar, 2015a, b; for A-level choices see Davies et al, 2017), most of them do not differentiate their analysis by gender.…”
Section: Income Information and Major Choice: Findings From Experimenmentioning
confidence: 99%
See 1 more Smart Citation
“…As labor market opportunities and earnings are significantly higher in mathrelated careers (11), many (mostly female) students who have a comparative advantage in reading but are nevertheless talented in math would have better career prospects in math-related fields. Hence, adequate information campaigns on future career prospects may be a welfare-improving way (because students can make better informed choices) of reducing the importance of the comparative advantage in students' decision making and, therefore, the gender gap in enrolment in math-related fields (35). Similarly, interventions involving teachers or parents targeted at limiting the role of the comparative advantage in educational choices could also be effective.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Therefore, this paper aims at providing an insight into the performance of freshmen university students in Italy. Our hypothesis is that gender differences can also vary among the different STEM courses: we are mindful of the recent work of Barone et al (2019) that has claimed the presence of a care-technical divide within STEM courses.…”
Section: Introductionmentioning
confidence: 99%